BF Enterprise: Banana Peel Flour / Siti Nur Hazimah Ibrahim...[et.al] - Ibrahim, Siti Nur Hazimah; Busran, Noor Diyanah; Hasan, Haslina; Muhamad, Nor Zairaa; Razman, Nur Solehah (Faculty of Plantation and Agrotechnology, 2016)
Entrepreneurship is a dynamic process that involves change and creation. Entrepreneurship can be defined as the identification, evaluation and exploitation of previously unexploited opportunities. The focus is on creation of a new enterprise or business as well as wealth associated with it. Essential dimensions or ingredients include willingness to take calculated risk. The skill to apply creative solutions and new ideas and finally, being pro-active to act on opportunities while others are still confused or unaware of the potential at hand. Banana peel flour is a new invention that had been created in Malaysia. It is a healthy flour that enriched with calcium, vitamin Band C. It is involving the simple processes which are cutting, drying, grinding and packaging.